2004
DOI: 10.3200/aeoh.59.8.392-399
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Noise on Blood Pressure and Heart Rate

Abstract: The authors assessed the acute effects of exposure to noise on systolic and diastolic blood pressure, and heart rate, among 46 workers in a midwestern auto assembly plant. Workers wore ambulatory blood pressure monitors and personal noise dosimeters during one work shift. After adjustment for covariates of cardiovascular function, systolic and diastolic blood pressure, along with heart rate, were shown to be significantly positively associated with noise exposure. Although the long-term effect of these associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
1
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 25 publications
4
92
1
7
Order By: Relevance
“…In our study, we found another special phenomenon that the prevalence of hypertension in women was significant higher than men, and the result was not consistent with the previous study [28]. The possible reasons were as follows: firstly, men both in noisy and non-noisy group did more physical work than women; secondly, fat accumulated with age and exorbitant fat of body was one of induced factors leading to hypertension, and body fat of women is higher than men with age increasing; thirdly, the questionnaires showed most of male workers had a drinking habit about 50 -100 ml/day, and only a few of them were used to drinking abuse.…”
Section: Discussioncontrasting
confidence: 47%
“…In our study, we found another special phenomenon that the prevalence of hypertension in women was significant higher than men, and the result was not consistent with the previous study [28]. The possible reasons were as follows: firstly, men both in noisy and non-noisy group did more physical work than women; secondly, fat accumulated with age and exorbitant fat of body was one of induced factors leading to hypertension, and body fat of women is higher than men with age increasing; thirdly, the questionnaires showed most of male workers had a drinking habit about 50 -100 ml/day, and only a few of them were used to drinking abuse.…”
Section: Discussioncontrasting
confidence: 47%
“…In industrybased studies, relationship between long-term occupational noise exposure and cardiovascular disorders such as myocardial infarction, coronary artery disease, and HTN has been observed 5,[7][8][9][10] . The results of some other studies among workers have shown the relationship between occupational noise exposure and increase in BP [11][12][13] . But the mechanism of this relationship is not clear.…”
Section: Introductionmentioning
confidence: 76%
“…However, transient increases in blood pressure have been clearly documented in several studies including studies where exposure was carried out under controlled laboratory conditions and studies using ambulatory blood pressure monitoring to assess work related and environmental noise (Baudrie et al, 2001;Andren et al, 1980;Isling and Michalak, 2004;Lusk et al, 2004;Haralabidis et al,2008;Chang et al, 2015). Haralabidis et al found that transient aircraft events were associated with acute rises in systolic and diastolic blood pressure of 6.2 mmHg and 7.4 mmHg respectively, with blood pressure measured at 15 minute intervals using non-invasive ambulatory monitoring (Haralabidis et al,2008).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there is a body of evidence documenting the associations between chronic noise exposure, hypertension and cardiovascular disease as described above, noise exposure also has acute effects on blood pressure, causing transient increases in systolic and diastolic blood pressure observed in laboratory and field conditions (Baudrie et al, 2001;Andren et al, 1980;Isling and Michalak, 2004;Lusk et al, 2004;Haralabidis et al,2008;Chang et al, 2015). One study which recorded ambulatory blood pressure at 15 minute intervals documented transient increases in blood pressure in normotensive adults specifically in relation to aircraft flight events near airports Haralabidis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%